دراسة بعض خصائص كومبوست القمامة وإمكانية استخدامه في الأوساط الزراعية لإنبات بعض النباتات الحراجية - علاء الدين, حسن; هيفا, سوسن; نيصافي, ابراهيم; حرفوش, شفق (Latakia University Journal -Biological Sciences Series, 2018)
some properties of compost garbage and its mixtures were studied in the laboratory, The agricultural media and mixtures have been tried in the agriculture field , Then results of agriculture were linked to their studied characteristics to determine their suitability and ways to improve them, The three mixtures were prepared (½ compost: ½ nursery soil, ¼ compost: ¾ nursery soil, ¾ compost : ¼ nursery soil) and the three Trials (compost, nursery soil, Turf) Half the number of these medias were sterilized by Alrodonnel and copper oxy chloride to determine the need for sterilization and the comparison between sterile and non-sterile samples. Then watering the compost well to minimize the salinity. Physical and chemical properties of compost and the rest of the media that were used were analyzed and the results showed good organic matter content and excellent proportion of (C / N) and a good content of small and large nutrients, but It has been noted the increase of salinity and the pH value The results also showed compost ability to improve the physical and chemical properties of the soil, we have planted the seeds of forest (Casuarina equisetifolia ،Jatropha curcas, Robinia pseudoacacia) and then we calculated the percentage of germination of the seeds planted and how the compost affect there growth. And the results showed that the mixtures (½ compost: ½ mixture nursery) has led to obtain a strong structure of the plant. تمت دراسة بعض الخصائص لكومبوست القمامة وخلائطه مخبرياً، وجرى تجريب هذه الأوساط في الزراعة الحقلية وربطت نتائج الزراعة عليها بخصائصها المدروسة لتحديد مدى صلاحيتها وطرق ومواد تحسينها. تم تحضير ثلاث خلائط وهي :( ½ كومبوست: ½ تربة مشتل)، (¼ كومبوست: ¾ تربة مشتل)، و(¾ كومبوست : ¼ تربة مشتل) واستخدمت ثلالة شواهد ( كومبوست، تربة ، و تورف). أيضاً تم تعقيم نصف عدد الخلطات الحاوية على الكومبوست بالرودونيل وأوكسي كلور النحاس لمعرفة مدى ضرورة التعقيم والمقارنة بين العينات المعقمة وغير المعقمة، ثم تم غسيل الكومبوست وأيضاً إشباعه بالماء للتقليل من كمية الأملاح الموجودة فيه، وتم القيام بتحليل الخصائص الفيزيائية والكيميائية للكومبوست وبقية الأوساط المستخدمة. أظهرت النتائج المحتوى الجيد من المادة العضوية ونسبة ممتازة لـ C/N ومحتوى جيد للعناصر الغذائية الصغرى والكبرى، ولكن لوحظ ارتفاع قيمة الملوحة وارتفاع قيمة الـ pH، كما أظهرت النتائج قدرة الكومبوست على تحسين الصفات الفيزيائية والكيميائية للتربة. وزرعت بذور بعض الأنواع الحراجية على هذه الأوساط (روبينيا,Robinia pseudoacacia وجاتروفاJatropha curcas وكازورينا Casuarina equisetifolia )، وًتم حساب نسبة الإنبات للبذور المزروعة وطول المجموع الخضري لمعرفة مدى تأثر نمو النباتات بمواصفات الكومبوست، وأظهرت النتائج أن استخدام خلطة ½ كومبوست + ½ تربة أدى للحصول على بنية قوية للنبات.